Agriculture's contribution to economic growth and development in rural Limpopo Province: a SAM multiplier analysis - Pfunzo, Ramigo (Stellenbosch : Stellenbosch University, 2017)
Thesis (MScAgric)--Stellenbosch University, 2017.